JOINTING MACHINE MAINTENANCE ANALYSIS USING RELIABILITY CENTERED MAINTENANCE (RCM) METHOD - Trio Yonathan Teja Kusuma; Yoga Aldi Pratama (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2020)
Maintenance activities must be carried out appropriately based on the type of machine and machine components. A machine consists of vital components, so that if the components of a machine are continuously subject to fatal damage, it can result in losses for the company. Proper maintenance activities can extend the service life of the machine and can minimize costs for maintenance of damaged machines. PT. Bakrie Pipe Industries is a company that produces steel pipes of various diameters. In producing steel pipes, PT. Bakrie Pipe Industries uses several machines. In 2019, there were several machines with the most frequent problems at Plant KT 24. The machine with the highest downtime of 2660 minutes was the Jointing Machine. In this study, a maintenance analysis was carried out using the Reliability Centered Maintenance (RCM) method on the Jointing Machine at Plant KT 24 PT. Bakrie Pipe Industries. In the results of selecting the maintenance task for the Jointing Machine critical components, it can be concluded that the Roller Blade component with the Potential Cause of Failure is broken Guide Wheel Bearing, the maintenance task is selected, namely Condition-Directed Task, Indexing Clamp component is Condition-Directed Task, Torch component is Condition-Directed Task, Nozzle component is Condition-Directed Task, Roller Blade component with the Potential Cause of Failure is Leaky Cylinder is Failure Finding Task, Bushing Torch component is Condition-Directed Task, and Cooler Torch Hose component is Failure Finding Task.